Targeting Acinetobacter baumannii resistance-nodulation-division efflux pump transcriptional regulators to combat antimicrobial resistance - Ruwani L. Wimalasekara; Dawn White; Ayush Kumar (npj Antimicrobials and Resistance)
Abstract Regulatory elements controlling gene expression fine-tune bacterial responses to environmental cues, including antimicrobials, to optimize survival. Acinetobacter baumannii, a pathogen notorious for antimicrobial resistance, relies on efficient efflux systems. Though the role of efflux systems in antibiotic expulsion are well recognized, the regulatory mechanisms controlling their expression remain understudied. This review explores the current understanding of these regulators, aiming to inspire strategies to combat bacterial resistance and improve therapeutic outcomes.